KEWAJARAN NILAI PASAR SAHAM PERUSAHAAN PASCA RIGHT ISSUE - Khoirudin, Rifki; Kusuma, Desta Rizky (EP FEB UNS, 2016)
This study aims to estimate the fair value per share of PT BW Plantation Tbk after the company offered right issue. This study is also intended to find out the fair market value per share of PT BW Plantation Tbk post-rights issue. The information used in this study was obtained from secondary data from the financial statements of PT BW Plantation Tbk., which were audited by public accountants and other information available in the financial statements. BW Plantation Tbk., The company's financial statements comparison, and the company's stock price data comparison. The methods of analysis used in determining the fair value per share is the Discounted Cash Flow and Relative Valuation. Discounted Cash Flow analysis was done by: projections of financial statements i.e. balance sheet and income statement, the projected Free Cash Flow to Equity (FCFE), the determination of the discount rate, the determination of Terminal Value, and the estimated fair value of equity. Analysis of Relative Valuation begins with finding the comparison companies in the same business line, select and assign the appropriate multiple of the comparison companies. Multiple used are: Price Earnings Ratio (PER), Price to Book Value (PBV), and Price to Sales Ratio (P / S).Keywords: valuation of shares, rights issue, discounted cash flow, relative valuation